PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Rubinem (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the low results of students' mathematics learning in class II SD Negeri 010 Silikuan Hulu. Out of 34 students, only 10 students, or 29.41%, were resolved. Based on this, the researchers conducted classroom action research with the aim of improving learning outcomes through the application of mathematical models of quantum teaching learning. This study was conducted over two cycles, each cycle consisting of two meetings and one daily test. The instruments used were the observation sheet activities of teachers and students, and a math achievement test. The data collection technique used was the technique of observation and tests of learning outcomes. The study states that the application of the quantum model of teaching can enhance the activity of teachers and students and mathematics learning outcomes for second-grade students at SD Negeri 010 Silikuan Hulu. This is supported by: (a) the activities of teachers in each cycle increase. In the first meeting of the first cycle, activities for teachers received a score of 35, or 67.3%, placing it in the "quite good" category. At the first meeting of the first cycle, activities for teachers received a score of 41, or 78.8%, placing it in the "good" category. At the first meeting of the second cycle, there was an increase with the acquisition of a score of 44, or 82.6%, with "very good" categories, and the second meeting of the second cycle obtained a score of 50, or 96.1%, with a "very good" category. Activities of students have increased. At the first meeting of the first cycle, activity students obtained a score of 28, or 58.3%, placing it in the "quite good" category. At the first meeting of the first cycle, activity students obtained a score of 34, or 70.8%, in the "good" category. At the first meeting of the second cycle, there was an increase with the acquisition of a score of 43, or 89.5%, with "very good" categories, and the second meeting of the second cycle obtained a score of 46, or 95.8%, to the category of "very good"; and (b) the results of students in each cycle have increased. The base score is the number of students who passed, with 21 students, representing a percentage of 61.7%, with the acquisition of an average value of 60.7. In the first cycle, the number of students who passed increased to 26 students, representing a percentage of 76.4%, with the acquisition of an average value of 83.3. In the second cycle, the number of students who passed increased to 34 students, representing a percentage of 88.23%, with an average value of 92.7.